Perancangan Virtual Prvate Network L2tp Dengan Mikrotik Untuk Remote Access Pada Kejaksaan Negeri Jakarta Barat - Maulana, Fajar; Qomaruddin, Muhammad (Jurnal Keilmuan Teknologi Informasi dan Ilmu Manajemen (Justifi), 2022)
With the increasing development of technology today, the need for information is increasing. Where everyone needs information in a fast, short, and accurate time. An agency or organization in carrying out its activities cannot be separated from the exchange of information between stakeholders with one another. A communication network is also very much needed at the West Jakarata District Attorney's office, as a means of communication for exchanging data and information. However, the presence of employees who carry out office activities outside the West Jakarta District Attorney is a problem because sometimes they have to return to the office to retrieve the data needed for work, where the data is on the local network inside the office, which results in inefficient work time. . Therefore, tools and networks are needed that can access data in the local office network anytime and anywhere the employee is located. Therefore, in this study, a Virtual Private Network network design was carried out with the Layer 2 Tunneling Protocol with IPsec as additional security, using Mikrotik. Which is a communication system on a computer network that allows a device to be connected directly using a public network, so that local networks can be accessed remotely. So that the configuration of the VPN server allows employees to remotely enter the office network from anywhere via a VPN server, which results in the conclusion that employees are more time efficient in doing their work. Because they can do office work such as creating or retrieving data and information needed in the local network of the West Jakarta District Attorney's office, and wherever they are.